Herpes Virus Pseudotumor in a Patient with HIV Immunosuppression - Daniel York; Pavan Patel; Smera Saikumar (Case Reports in Obstetrics and Gynecology)
Background. In rare cases, HSV infections can present as pseudotumors that are often mistaken as malignancies in patients with an uncontrolled HIV infection. Herpes simplex virus type 2 (HSV-2) infection rates range from 60% to 90% in individuals coinfected with HIV. Case Presentation. A 48-year-old patient presented with a large fungating mass near her right inferior vulva with a hardness of surrounding tissues. The mass was 4 cm×3 cm in size and was excised in the operating room. The pathology was negative for malignancy; however, it showed lymphoplasmacytic proliferation with immunostaining positive for HSV virus. Conclusion. Atypical HSV pseudotumors should be considered in the differential diagnosis for an immunosuppressed patient who presents with a genital mass lesion.